DUKUNGAN SOSIAL DAN CULTURE SHOCK PADA MAHASISWA RANTAU ASAL KALIMANTAN DI SALATIGA - William Andre,; Arthur Huwae, (Jurnal Cakrawala Ilmiah, 2022)
Being in a new environment for some people is a stimulus that will later lead to new problems. Culture shock, in particular, happens to students from Kalimantan who study at UKSW Salatiga. The significant difference between cultural habits and geographical differences between Kalimantan and Salatiga is a challenge for overseas students from Kalimantan. So the need for a strategy to reduce the culture shock experienced by overseas students from Kalimantan is with social support from their new environment. This study aims to determine the relationship between social support and culture shock in overseas students from Kalimantan in Salatiga. The method used is quantitative with a correlational design. The subjects taken were 50 students from Kalimantan who studied at UKSW Salatiga. The sampling technique used in this study was non probability. Research measurements used The Multidimensional Scale of Perceived Social Support and the culture shock scale compiled by Purba (2017). The research data analysis method uses Karl Pearson's product moment correlation. The results of the study through the correlation test showed a correlation coefficient of -0.727 with a significance of 0.000 (p <0.05) which means that there is a significant negative relationship between Social Support and Culture Shock, so this study's hypothesis is accepted. These results mean that the higher the Social Support, the lower the Culture Shock, and vice versa, the lower the Social Support, the higher the Culture Shock.